EFFECTIVENESS TESTS OF VEGETABLE INSECTICIDES ESSENTIAL OILS OF MUTMET SEED (Myristica fragrans Houtt.) AND CLOVE FLOWER (Syzygium aromaticum L.) ON RICE BEETLE MORTALITY AND DEVELOPMENT Sitophilus oryzae (Linnaeus, 1763) - Fadhila, Fasya; Hariani, Nova; Patang, Fatmawati (Universitas Tanjungpura, 2023)
This study aims to analyze the inhibition of the development of the F1 generation of rice beetles by nutmeg and clove flower essential oils, and to determine the mortality of rice beetles against nutmeg and clove flower essential oils. The stages of the research started from rearing the rice beetle, preparing test insects, making variations in doses, treatments, and analysis. Two tests were conducted in the study, the first for inhibition of F1 generation activity and the percentage of mortality using the contact method (filter paper). The results showed that nutmeg and clove oil had an effect on the inhibition of the rice beetle F1 generation. Nutmeg oil has the best inhibition power with the percentage of F1 generation inhibition up to 100%. The mortality test using the filter paper method showed that for 48 hours nutmeg essential oil was able to kill rice beetles at all concentrations, namely 5-20% to 100%, while the percentage of 100% mortality was only found in the treatment with clove oil at the highest concentration (20%). The results showed that nutmeg oil showed better results than clove oil for controlling S. oryzae warehouse pests.